Rattus leucopus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
719. Cape York Rat Rattus leucopus French: Rat de Cape York / German: Kap-York-Ratte / Spanish: Rata de York Other common names: Mottle-tailed Rat, Mottle-tailed Cape York Rat, Spiny-furred Rat Taxonomy. Acanthomys leucopus Gray, 1867, “North Australia [Queensland]; Cape York.” Rattus leucopus is basal to the rest of the Australian species within Rattus, which are altogether sister to the Recent New Guinea species. Taxonomic revision is needed for R. leucopus and all other species in New Guinea, and R. leucopus might represent multiple species. Five subspecies recognized. Subspecies and Distribution. R.l.leucopusGray,1867—NCapeYork,Queensland, Australia. R.l.cooktownensisTate,1951—SECapeYork,Queensland,Australia. R.l.doboduraeTroughton,1946—SENewGuinea. R. l. ratticolorJentink, 1908 — SW New Guinea, probably including the Aru I. R. l. ingens Peters & Doria, 1880 — SC New Guinea. Descriptive notes. Head-body 135-210 mm,tail 140-210 mm, ear 18-24 mm, hindfoot 33-40 mm; weight 90-205 g. The Cape York Rat is ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 849-850, DOI: 10.5281/zenodo.6887260 ...